General LQG Homing Problems in One Dimension. (2nd October 2012) - Lefebvre, Mario; Zitouni, Foued
Abstract : Optimal control problems for one-dimensional diffusion processes in the interval (d 1, d 2 ) are considered. The aim is either to maximize or to minimize the time spent by the controlled processes in (d 1, d 2 ). Exact solutions are obtained when the processes are symmetrical with respect tod ∗ ∈ ( d 1, d 2 ) . Approximate solutions are derived in the asymmetrical case. The one-barrier cases are also treated. Examples are presented.